2021
DOI: 10.1038/s41598-021-92473-9
|View full text |Cite
|
Sign up to set email alerts
|

Crayfish hemocytes develop along the granular cell lineage

Abstract: Despite the central role of hemocytes in crustacean immunity, the process of hemocyte differentiation and maturation remains unclear. In some decapods, it has been proposed that the two main types of hemocytes, granular cells (GCs) and semigranular cells (SGCs), differentiate along separate lineages. However, our current findings challenge this model. By tracking newly produced hemocytes and transplanted cells, we demonstrate that almost all the circulating hemocytes of crayfish belong to the GC lineage. SGCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 59 publications
1
26
1
Order By: Relevance
“…In our short-term in vitro experiments, nuclear BrdU labeling was evident only in the hyaline cells, which were quite numerous, in contrast to reports in other species (e.g., Li et al., 2021 ). Nuclear BrdU was found in 10–15% of hyaline cells that were identified, suggesting that this population is active in the cell cycle ( Figures 4 A–4C).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In our short-term in vitro experiments, nuclear BrdU labeling was evident only in the hyaline cells, which were quite numerous, in contrast to reports in other species (e.g., Li et al., 2021 ). Nuclear BrdU was found in 10–15% of hyaline cells that were identified, suggesting that this population is active in the cell cycle ( Figures 4 A–4C).…”
Section: Resultscontrasting
confidence: 99%
“…It has been reported that circulating hemocytes in crayfish proliferate rarely ( Bauchau, 1981 ; Söderhäll et al., 2003 ; Li et al., 2021 ). We wanted to test this in P. clarkii , because this has important implications for these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Another reason for the change in the proportions of the hemocyte types might also be the conversion between the main hemocyte types (e.g., granule accumulation or degranulation). For instance, some studies have indicated that the different types of hemocytes represent different stages of hemocyte development ( 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the hyaline cell is not yet resolved. Li et al (2021) recently proposed an alternative model of haematopoiesis for crayfish Cherax quadricarinatus in which the circulating haemocytes belong to one lineage. Semigranulocytes and granulocytes were interpreted as different developmental stages rather than two types of fully differentiated cells.…”
Section: ) E-cells Of the Hepatopancreasmentioning
confidence: 99%